Gene Expression Profiling of Chondrogenic Markers in Cultures Ovine Chondocytes - Nishanthoka Jesslyn, C.M.; G. Suganya; V. Leela; Sabiha Hayath Basha (The Indian Veterinary Journal, 2026)
This study investigated the ability of ovine chondrocytes to maintain their chondrogenic potential at different passage levels under in vitro culture conditions using real-time PCR. Articular cartilage tissue was collected from apparently healthy sheep from a local slaughterhouse. Chondrocytes were isolated from the articular tissue using enzymatic digestion. The isolated chondrocytes were cultured using suitable media and conditions till passage 3. The cultured chondrocytes were characterized by real-time PCR using chondrogenic markers, namely Collagen type – II (COLII), Aggrecan (AGC), and Collagen type – I (COLI). There was a significant (p < 0.01) decrease in the mRNA expression of COLII in passaged cells when compared to the primary culture. The mRNA expression of COLI increased with increasing passage number. Thus, from this study, it was evident that ovine chondrocytes get dedifferentiated into a fibroblast phenotype with increasing passage number. This simple and reliable assessment can thus be used to screen cultured chondrocytes for deviation from their chondrogenic phenotype to be used for tissue engineering applications.